Light-related photosynthetic characteristics of freshwater rhodophytes - Necchi, O. (Elsevier B.V., 2005)
Photosynthetic characteristics in response to irradiance were analysed in 21 field and culture populations of thirteen freshwater red algal species applying two distinct techniques (chlorophyll fluorescence and oxygen evolution). Photosynthesis-irradiance (PI) curves indicated adaptations to low irradiances in all species analysed, essentially characterized by occurrence of photoinhibition, low values of the saturation parameter (I-k < 225 mu mol m(-2) s(-1)) and compensation irradiance (I-c < 20 mu mol m(-2) s(-1)) and relatively high values of the effective quantum yield of photosystem II (Delta F/F'(m) >= 45). These characteristics have been reported in freshwater red algae and were confirmed from data based on the two techniques, indicating they are typically shade-adapted plants. on the other hand, some species (e.g. Batrachospermum delicatulum) can tolerate high irradiances (up to 2400 mu mol m(-2) s(-1)), suggesting they have mechanisms that enable them to avoid photodarnage of the photosynthetic apparatus. One of these mechanisms is the increase in dissipation of excessive energy captured by reaction centres after exposure to continuous irradiance, as reflected by the non-photochemical quenching fluorescence parameter in dark/light induction curves. Photo-inhibition occurred in all algae tested by both techniques. Light acclimation was evident particularly in field populations, as revealed by lower values of the saturation parameter (Ik) and the compensation irradiance (I-c) and higher values of Delta F/F'(m) in algae under low irradiances (shaded or heavily shaded stream segments), and vice-versa. Forms living within the boundary layer (e.g. crusts), in a region of reduced current velocity, tended to be more shade-adapted than semi-erect plants (e.g. non-mucilaginous or mucilaginous filaments), as indicated by highest values of photosynthetic efficiency (alpha = 0.31) and effective quantum yield (Delta F/F'(m) = 0.88) under natural conditions. Higher photo- synthetic rates (P-max) for the same species or population were observed under culture than field conditions when measured with the oxygen evolution technique, whereas the opposite trend was observed using chlorophyll fluorescence. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chlorophyll fluorescence; irradiance; oxygen evolution; photosynthesis; Freshwater; Rhodophyta; lotic algae